2020
DOI: 10.1101/2020.09.10.292482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The organosulfur compound dimethylsulfoniopropionate (DMSP) is utilized as an osmoprotectant byVibriospecies

Abstract: Dimethylsulfoniopropionate (DMSP) is a key component of the global geochemical sulfur cycle that is a secondary metabolite produced in large quantities by marine phytoplankton and utilized as an osmoprotectant. Bacterial DMSP lyases convert DMSP to the climate active gas dimethylsulfide (DMS). Whether marine bacteria can also accumulate DMSP as an osmoprotectant to maintain the turgor pressure of the cell in response to changes in external osmolarity remains unknown. The marine halophile Vibrio parahaemolyticu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Given the abundance of DMSOP in the salt marsh sediments, above, and that Thume et al demonstrated that diverse bacteria import DMSOP 1 , we proposed that diverse microorganisms could utilise it as an osmoprotectant, as was known to be the case for its precursor molecule DMSP 17,18 . To test this hypothesis, the osmosensitive E. coli strain, FF4169, deficient in trehalose production 19 , was grown under saline conditions in the presence and absence of DMSOP, DMSP and the nitrogenous osmoprotectant glycine betaine (GB).…”
Section: Mainmentioning
confidence: 79%
“…Given the abundance of DMSOP in the salt marsh sediments, above, and that Thume et al demonstrated that diverse bacteria import DMSOP 1 , we proposed that diverse microorganisms could utilise it as an osmoprotectant, as was known to be the case for its precursor molecule DMSP 17,18 . To test this hypothesis, the osmosensitive E. coli strain, FF4169, deficient in trehalose production 19 , was grown under saline conditions in the presence and absence of DMSOP, DMSP and the nitrogenous osmoprotectant glycine betaine (GB).…”
Section: Mainmentioning
confidence: 79%
“…The marine halophile Vibrio parahaemolyticus contains four BCCT carriers (BccT1 to BccT4). It is indicated that BccT1 and BccT2 are carriers of DMSP in V. parahaemolyticus , whereas BccT3 and BccT4 do not play a significant role in DMSP transport in V. parahaemolyticus (Gregory et al ., 2020). Of the four additional Vibrio species that used DMSP as an osmolyte, V. harveyi and V. fluvialis contain homologues of BccT1 and BccT2 while V. vulnificus and V. cholerae can utilize DMSP as an osmolyte and contained only a BccT3 homologue.…”
Section: Dmsp Transportmentioning
confidence: 99%
“…Of the four additional Vibrio species that used DMSP as an osmolyte, V. harveyi and V. fluvialis contain homologues of BccT1 and BccT2 while V. vulnificus and V. cholerae can utilize DMSP as an osmolyte and contained only a BccT3 homologue. In V. vulnificus strains, an additional BCCT family transporter, named BccT5, was also a carrier for DMSP (Gregory et al ., 2020). The second transporter family found to carry DMSP across the membrane is the ATP binding cassette (ABC) transporter, a commonly used primary transporter that can be found in all three domains of life (Eitinger et al ., 2011).…”
Section: Dmsp Transportmentioning
confidence: 99%